Effect of different intensities of glycemic control on maternal and fetal outcome in women with diabetes in pregnancy - M, Laxmi Devi; Prasad, Madhav; Mukhtar, Lubna (Nepal Journal of Obstetrics and Gynaecology, 2022)
Aims: To compare the feto-maternal outcomes between patients who have achieved different glucose target values after intervention for hyperglycemia in pregnancy. Methods: A prospective comparative observational study was conducted in the Obstetrics Department of a Teaching Hospital. The main outcome parameters were the values of the fasting blood sugar (FBS) and the postprandial blood sugars (PPBS) obtained from the self-monitoring tests. The patients were grouped into two groups – the tight control group-I and less tight control group-II. maternal and neonatal parameters are compared. Pearson’s chi-square test was used for proportions and unpaired t-test was used for numbers after checking for normality of distribution and p-value of <0.05 was taken as statistically significant. Results: Average values of FBS/PPBS values were lesser in group I (84/120) compared to group II (93/142).The proportion of maternal and fetal complications (hypertensive disorders, polyhydramnios, macrosomia, neonatal hypoglycemia, hyperbilirubinemia, NICU admission) were similar between the two groups. The average gestational age at delivery (38.2 weeks vs 37.7 weeks), the proportion of LSCS (50% vs 66.7%) and neonatal birth weight (2.88 kg vs 2.98 kg) were similar in both groups. Conclusion: There is no difference in feto-maternal outcome in between well controlled lesser control of blood sugar